Functional and Proteomic Analysis of Streptococcus pyogenes Virulence Upon Loss of Its Native Cas9 Nuclease - Gao, Nina J.; Al-Bassam, Mahmoud M.; Poudel, Saugat; Wozniak, Jacob M.; Gonzalez, David J.; Olson, Joshua; Zengler, Karsten; Nizet, Victor; Valderrama, J. Andrés (Frontiers in Microbiology, 2019)
The public health impact of Streptococcus pyogenes (group A Streptococcus, GAS) as a top 10 cause of infection-related mortality in humans contrasts with its benefit to biotechnology as the main natural source of Cas9 nuclease, the key component of the revolutionary CRISPR-Cas9 gene editing platform. Despite widespread knowledge acquired in the last decade on the molecular mechanisms by which GAS Cas9 achieves precise DNA targeting, the functions of Cas9 in the biology and pathogenesis of its native organism remain unknown. In this study, we generated an isogenic serotype M1 GAS mutant deficient in Cas9 protein and compared its behavior and phenotypes to the wild-type parent strain. Absence of Cas9 was linked to reduced GAS epithelial cell adherence, reduced growth in human whole blood ex vivo, and attenuation of virulence in a murine necrotizing skin infection model. Virulence defects of the GAS ∆cas9 strain were explored through quantitative proteomic analysis, revealing a significant reduction in the abundance of key GAS virulence determinants. Similarly, deletion of cas9 affected the expression of several known virulence regulatory proteins, indicating that Cas9 impacts the global architecture of GAS gene regulation.